Power of attorney of Alexander Skeene - Skene, Alexander, active 1739.
Power of attorney for Skene granted to James Crokatt by the colony of South Carolina together with plat of land owned by Skene in Craven County, N.C.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Crokatt, James; Land tenure -- North Carolina -- Craven County; Power of attorney -- South Carolina; North Carolina -- History -- Colonial period, ca. 1600-1775.; South Carolina -- History -- Colonial period, ca. 1600-1775.